Training-related brain plasticity in subjects at risk of developing Alzheimer’s disease - Belleville, Sylvie; Clément, Francis; Mellah, Samira; Gilbert, Brigitte; Fontaine, Francine; Gauthier, Serge (Brain (London, England : 1878), 2011)
Subjects with mild cognitive impairment are at risk of developing Alzheimer's disease. Cognitive stimulation is an emerging intervention in the field of neurology and allied sciences, having already been shown to improve cognition in subjects with mild cognitive impairment. Yet no studies have attempted to unravel the brain mechanisms that support such improvement. This study uses functional magnetic resonance imaging to measure the effect of memory training on brain activation in older adults with mild cognitive impairment and to assess whether it can reverse the brain changes associated with mild cognitive impairment. Brain activation associated with verbal encoding and retrieval was recorded twice prior to training and once after training. In subjects with mild cognitive impairment, increased activation was found after training within a large network that included the frontal, temporal and parietal areas. Healthy controls showed mostly areas of decreased activation following training. Comparison with pre-training indicated that subjects with mild cognitive impairment used a combination of specialized areas; that is, areas activated prior to training and new alternative areas activated following training. However, only activation of the right inferior parietal lobule, a new area of activation, correlated with performance. Furthermore, the differences between the brain activation patterns of subjects with mild cognitive impairment and those of healthy controls were attenuated by training in a number of brain regions. These results indicate that memory training can result in significant neural changes that are measurable with brain imaging. They also show that the brains of people with mild cognitive impairment remain highly plastic.